OPTIMIZATION OF Eucalyptus pellita F. Muell GROWTH USING ARBUSCULAR MYCORRHIZA FUNGI AND COFFEE HUSK COMPOST ON SUBSOIL MEDIA - Harmawati Harmawati; Syamsuddin Millang; Samuel Pembonan; Retno Prayudyaningsih (BIOTROPIA, 2025)
HIGHLIGHTS- Mycorrhizal fungi and coffee compost boost tree seedling growth in poor subsoil- The method helps grow Eucalyptus faster for land restoration efforts.- Reduces the need for topsoil, promoting sustainable nursery practices.- An optimal mix of mycorrhizal fungi and compost supports robust Eucalyptus development.ABSTRACTArbuscular mycorrhizal fungi (AMF) and coffee husk compost are used to improve the physical and chemical conditions of the subsoil, enhancing plant growth. This study aimed to evaluate the response of plant growth and analyze the effect of AMF and coffee husk compost doses on optimal growth acceleration of Eucalyptus pellita seedlings in subsoil media. Seedlings were grown in subsoil with varying doses of AMF (0; 2.5; and 5 g/polybag) and coffee husk compost at different ratios (1 : 1; 2 : 1; and 3 : 1). AMF and coffee husk compost application significantly affected all parameters of seedling growth, including height, number of leaves, diameter, biomass, seedling quality index, and shoot/root ratio. Inoculation of AMF at a dose of 2.5 g/polybag and subsoil media enriched with coffee husk compost at a ratio of 2 : 1 was an efficient treatment to increase the seedling growth